Optimization of digital media utilization by applying ANEKA values in the learning process at MIN 4 Pringsewu - Lisa Apriyani (Science Center Group, 2025)
Background: Low student learning motivation remains a critical challenge in primary education, particularly in thematic learning contexts where instructional delivery often lacks media variation. The integration of digital learning media, aligned with core civil service values (ANEKA: Accountability, Nationalism, Public Ethics, Quality Commitment, and Anti-Corruption), offers a strategic approach to enhancing student engagement and instructional quality. Objective: This study aimed to optimize the utilization of digital media in the learning process by integrating ANEKA values to improve students’ learning motivation at MIN 4 Pringsewu, Lampung, Indonesia. Methods: A descriptive quantitative survey design was employed involving 24 fourth-grade students. The intervention consisted of eight structured activities, including teacher socialization, student personal engagement, national song integration using digital media, interactive games and ice breaking, optimization of PowerPoint presentations, animated videos, hologram media utilization, and structured student feedback collection. Data were analyzed using descriptive statistics based on student feedback responses. Results: The implementation of digital media integrated with ANEKA values demonstrated a positive impact on student motivation. Feedback analysis indicated that 87.5% of students expressed positive responses, reporting increased enthusiasm, engagement, and interest in learning activities. Conclusion: The optimization of digital learning media, when systematically integrated with professional ethical values, effectively enhances student learning motivation. This approach not only strengthens instructional engagement but also reinforces accountability, quality commitment, and ethical educational practices in primary school settings.